Knowledge and Attitudes Regarding Infant Feeding Practices and Their Correlation with Stunting in Toddlers at Kesunean Community Health Center, Cirebon - Thysa Thysmelia Affandi; Fitriani, Hikmah; Fitriani, Emallia (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Stunting is a form of chronic malnutrition characterized by impaired growth and development in children, which occurs due to prolonged inadequate nutritional intake. Based on data from the 2018 Indonesian Basic Health Research (RISKESDAS), the prevalence of stunting in Indonesia reached 29.2%, surpassing the World Health Organization (WHO) acceptable threshold of 20%. The occurrence of stunting is influenced by various factors, one of the most crucial being maternal knowledge and attitudes toward breastfeeding and complementary feeding practices. This study aimed to analyze the level of knowledge and attitudes among mothers regarding these feeding practices for toddlers at the Kesunean Community Health Center in Cirebon City. Utilizing a descriptive-analytical approach with a cross[1]sectional design, the study involved 281 mothers with toddlers aged 24 to 60 months, selected through purposive sampling. Data were gathered using structured questionnaires and analyzed using the Spearman correlation test. The results showed a significant negative correlation between maternal knowledge and the incidence of stunting (p = 0.000; r = -0.428), indicating that higher knowledge levels were associated with lower stunting rates. Additionally, a significant negative correlation was also found between maternal attitudes and stunting (p = 0.000; r = -0.451), suggesting that positive maternal attitudes contribute to better nutritional outcomes. Overall, the majority of mothers demonstrated sufficient knowledge and positive attitudes toward breastfeeding and complementary feeding. These findings emphasize the importance of strengthening maternal education programs to enhance awareness and improve nutritional practices for preventing stunting in toddler